Peran Guru Pendidikan Agama Islam dalam Membimbing Kecerdasan Spiritual Melalui Budaya Religius - Dwi Cahya, Afrilia; Mulyadi, Mus; Nurhadi (JPT : Jurnal Pendidikan Tematik, 2022)
The background of this research is to find out the role of Islamic religious education teachers in guiding spiritual intelligence through religious culture at the Insan Kamil Islamic School Bengkulu. This type of research is qualitative with a qualitative descriptive method. The primary data sources in this study were Islamic religious education teachers. Data collection techniques using observation, interviews and documentation. Then to check the validity of the data using triangulation, namely comparing the data found with existing sources. Data analysis and management were taken when the researcher was in the field and after collecting data from the field. The results of this study indicate that Islamic religious education teachers in guiding the spiritual intelligence of students through religious culture at the Insan Kamil Islamic School Bengkulu Elementary School, Islamic religious education teachers carry out their roles by working together to be actively involved in supervising students at congregational prayers at school. Then through religious culture at the Insan Kamil Islamic School Bengkulu, Islamic religious education teachers also always motivate students by telling Islamic stories to students, and Islamic religious education teachers carry out their role as evaluators by providing evaluation books of worship and moral activities carried out in the school. home, because Islamic religious education teachers at the Bengkulu Insan Kamil Islamic School Elementary School assess students not only from the cognitive aspect, but also from the attitude aspect carried out by students at home as one of the evaluations for Islamic religious education teachers at the Insan Kamil Elementary School. Islamic School Bengkulu.